Knee strength, hop performance and self-efficacy at 4 months are associated with symmetrical knee muscle function in young athletes 1 year after an anterior cruciate ligament reconstruction - Susanne Beischer; Eric Hamrin Senorski; Christoffer Thomeé; Kristian Samuelsson; Roland Thomeé (BMJ Open Sport & Exercise Medicine)
Objectives We investigated whether patient demographics, 4-month patient-reported outcomes (PRO) and muscle function predicted young athletes regaining symmetrical muscle function in five tests of muscle function 1 year after ACL reconstruction.Methods We extracted data on patient demographics, PROs and the results of five tests of muscle function from a rehabilitation-specific register. Athletes were 15–30 years of age, involved in knee-strenuous sport and had undergone a primary ACL reconstruction. The primary outcome was achieving a Limb Symmetry Index of ≥90% for the battery of tests 1 year after ACL reconstruction. Patient demographics, muscle-function data and results for PROs at the 4-month follow-up were analysed.Results In all, 237 athletes (59% female; mean age 22±4 years) were included in the study. One year after ACL reconstruction, 26% (62/237) of the included athletes had achieved symmetrical muscle function. Univariable analysis showed that symmetrical muscle function was associated with present self-efficacy, OR 1.28 (95% CI 1.04 to 1.58, p=0.011), knee-extension strength, OR 1.73 (95% CI 1.28 to 2.34), knee-flexion strength, OR 1.39 (95% CI 1.07 to 1.81), vertical hop, OR 1.77 (95% CI 1.27 to 2.45), single-leg hop for distance, OR 1.98 (95% CI 1.24 to 3.17) and side hop, OR 1.64 (95% CI 1.15 to 2.33).Conclusion Symmetrical knee-extension and knee-flexion strength, a more symmetrical hop performance and higher present self-efficacy at an early stage all increased the odds of achieving symmetrical muscle function in young athletes 1 year after ACL reconstruction.